Thursday

July 24, 2014

July 24, 2014

Posted by **Katie** on Saturday, March 3, 2012 at 5:37pm.

- Trig -
**Steve**, Sunday, March 4, 2012 at 11:28amsin/(cos+1) + (cos-1)/sin

= [sin*sin + (cos-1)(cos+1)]/[sin(cos+1)]

= (sin^2 + cos^2 - 1)/[sin(cos+1)]

= (1-1)/[sin(cos+1)]

= 0

**Related Questions**

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

Pre-calc - prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...